Sustainable employee green behavior in the workplace: Integrating cognitive and non‐cognitive factors in corporate environmental policy. (16th August 2021) - Sabbir, Md. Mahiuddin; Taufique, Khan Md Raziuddin
Abstract: Sustaining employee green behavior (EGB) in the workplace requires an inclusive understanding of the factors that induce it. This study aims to bridge the gap of scarce research on task‐related EGB by integrating both cognitive and non‐cognitive factors as an extension to the theory of planned behavior. Task‐related EGB refers to employees pro‐environmental behaviors performed as part of routine tasks and roles. Using principal component analysis and structural equation modeling, the survey findings from 302 employee participants reveal that both cognitive and non‐cognitive factors significantly influence the task‐related EGB. In addition to this theoretical contribution, this study's findings suggest that creating positive environmental attitudes and habits via pro‐environmental policies, procedures, and practices in the workplace can enhance employees' task‐related EGB. The provision of access to information, training, and other resources regarding pro‐environmental behavior in the workplace may also have an impact. Besides, the results validate the underexplored mediating role of environmental attitudes and pro‐environmental habits between individual‐level predictors and task‐related EGB in the workplace. Lastly, this study's findings offer potential directions for further research in relation to EGB in the workplace.